Mining Impact on Livelihoods of Farmers of Asutifi North District, Ghana - Agariga, Felix; Abugre, Simon; Siabi, Ebenezer K.; Appiah, Mark (Environmental Management and Sustainable Development, 2021)
Local communities in Ghana are heavily reliant on agriculture for their livelihoods. However, they are increasingly shifting from engaging in agriculture to mining. This study was undertaken to assess the impact of mining (both small and large scale) on the livelihoods of community members of Kenyasi, Asutifi North District in Ghana. Data were collected from 201 farming households who were selected randomly and interviewed for a variety of information. The questionnaire responses received from the respondents were classified into items and each item’s responses were tallied. The results of the studies show that the farmers’ livelihood systems were affected by the mining operations occurring around their communities. Water pollution, displacement of farmers from their lands, degradation of agricultural lands, and an increase in social vices and higher dropout rates of students from schools are some of the reported consequences of the mining activities. The pollution of the water resources poses a serious threat to the health and livelihood systems of these farmers as they depend on the water resources for agriculture and domestic use. In this study, we project that there could be increased grievances over scarce land resource and food insecurity that could lead to conflicts in the mining areas. The lack of land resources could have a tremendous effect on the social, economic, and political climate of a country and must be considered and addressed as some of the most immediate threats to Ghana’s national security.